Barriers, incentive mechanisms, and roles of institutions in scaling climate smart agriculture and climate information services - Dossou-Yovo, Elliott Ronald; Arouna, Aminou; Bryan, Elizabeth; Ringler, Claudia; Mujawamariya, Gaudiose; Benfica, Rui; Freed, Sarah; Yossa, Rodrigue (Accelerating Impacts of CGIAR Climate Research for Africa, 2022)
This study uses a framework that provides ample space for local stakeholders to integrate their knowledge and experience in the assessment of the barriers, incentives mechanisms, and roles of institutions for scaling out locally relevant CSA interventions in the four rice-growing environments in Mali. The study found that the adoption levels of many CSA interventions have been low. The barriers to large-scale adoption of CSA interventions were specific to the rice growing environments and interventions, but overall included the lack of funding, equipment, capacity for implementation, cost of technology, insufficient fertilizer, quality seeds, and low awareness of farmers of the benefits of the interventions. Stakeholders emphasized the importance of subsidies, capacity building, and access to extension services as essential incentive mechanisms, and governments, farmers' organizations, women's organizations, youth organizations, and research and academic institutions as key players for scaling CSA interventions at the local level.